2020
DOI: 10.3390/nano10101961
|View full text |Cite
|
Sign up to set email alerts
|

Surface Treatment of Cu:NiOx Hole-Transporting Layer Using β-Alanine for Hysteresis-Free and Thermally Stable Inverted Perovskite Solar Cells

Abstract: Inverted perovskite solar cells (PSCs) using a Cu:NiOx hole transporting layer (HTL) often exhibit stability issues and in some cases J/V hysteresis. In this work, we developed a β-alanine surface treatment process on Cu:NiOx HTL that provides J/V hysteresis-free, highly efficient, and thermally stable inverted PSCs. The improved device performance due to β-alanine-treated Cu:NiOx HTL is attributed to the formation of an intimate Cu:NiOx/perovskite interface and reduced charge trap density in the bulk perovski… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…We have reported the solution combustions synthesis of pristine and co-doped (Cu, Li) NiCo 2 O 4 films, applying a 300 • C annealing temperature and incorporating them as high performance HTLs in MAPbI 3 -based inverted perovskite solar cells [38,39]. We have also shown the improvements of PVSC's thermal stability based on SCS Cu:NiO x HTL by treatment of Cu:NiO x with β-alanine, showing a T80 of 1000 h under heat conditions (60 • C, N 2 ), as well as the improvement of humidity degradation resistance for SCS NiO x -based PVSC with the addition of 1% Nitrobenzene within the perovskite active layer [40,41]. Jae Woong Jung et al have reported the solution combustion synthesis of the Cu:NiO x film at 150 • C and implemented it as HTL in MAPbI 3 perovskite solar cell.…”
Section: Introductionmentioning
confidence: 62%
“…We have reported the solution combustions synthesis of pristine and co-doped (Cu, Li) NiCo 2 O 4 films, applying a 300 • C annealing temperature and incorporating them as high performance HTLs in MAPbI 3 -based inverted perovskite solar cells [38,39]. We have also shown the improvements of PVSC's thermal stability based on SCS Cu:NiO x HTL by treatment of Cu:NiO x with β-alanine, showing a T80 of 1000 h under heat conditions (60 • C, N 2 ), as well as the improvement of humidity degradation resistance for SCS NiO x -based PVSC with the addition of 1% Nitrobenzene within the perovskite active layer [40,41]. Jae Woong Jung et al have reported the solution combustion synthesis of the Cu:NiO x film at 150 • C and implemented it as HTL in MAPbI 3 perovskite solar cell.…”
Section: Introductionmentioning
confidence: 62%
“…While NiO X is used as a p-type metal oxide in PSCs for superior long-term stability compared to organic or polymeric HTM, 52 the instability of NiO X is also frequently reported particularly in the presence of oxygen with varying oxidation states. 53,54 The generated oxygen vacancies in NiO X could induce the photooxidation of the neighboring perovskite film. 55 In Figure S5, PSCs stored in the absence of oxygen still bring a more prominent J SC decrease for NiO X by 6% over 440 h compared to a 1% reduction for pTPD, which underlines that the significant difference in ambient air with humidity (Figure 3(a)) would be dominantly ascribed to the lattice strain effect rather than the difference in substrate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Figure 6 a, the PL emission peak shifts from 770 nm to 766 nm after GABr treatment, which is in keeping with the absorption spectra. Moreover, the intensity of PL peak of GABr-treated film is much stronger than the pristine film, suggesting a superior film with fewer density of defects and suppressed nonradiative recombination (as shown in Figure 6 b) [ 49 , 50 , 51 ]. The TRPL curve can be fitted by a biexponential equation [ 23 ]: f(t) = A 1 exp(−t/τ 1 ) + A 2 exp(−t/τ 2 ), where τ 1 , τ 2 refer to the fast-decay and long-decay recombination mechanism, A 1 , A 2 are the corresponding coefficients.…”
Section: Resultsmentioning
confidence: 99%